Horseback Riding Improves the Ability to Cause the Appropriate Action (Go Reaction) and the Appropriate Self-control (No-Go Reaction) in Children - Ohtani, Nobuyo; Kitagawa, Kenji; Mikami, Kinuyo; Kitawaki, Kasumi; Akiyama, Junko; Fuchikami, Maho; Uchiyama, Hidehiko; Ohta, Mitsuaki (Frontiers in Public Health, 2017)
Background There are many obvious health benefits to riding, including developing a strong core and legs, but there are also many less obvious benefits, such as increased confidence and introspection. Few studies have addressed the effects of horseback riding on children and the mechanisms underlying how riding affects humans. We examined the effects of horseback riding on the ability to distinguish Go/No-go tasks and solve arithmetic problems in children. Methods The subjects were 34 boys and 72 girls, aged 10–12 years old, that were divided into three groups (horse riding, walking and resting). They were healthy typical children, who performed the Go/No-go tasks and solved the arithmetic problems. The heart rate and heart rate variability of the children, and the three-dimensional acceleration of the children while walking horses, were examined . Results Riding on a half-breed horse or a pony improved the ability to perform Go/No-go tasks and solve arithmetic problems, possibly through sympathetic activity. Some horses, like the Kiso, might provide a healing effect to children through parasympathetic activity. Statistically significant differences in the three-dimensional acceleration and the autonomic activities were observed among the three horses. The acceleration in the Kiso horse group during walking in hand was significantly different from those involving the other two horses, indicating that the vibrations produced by these horses might modify the autonomic activities. Conclusion The most important beneficial factor of horseback riding for children and for human health appears to be associated with the horse’s vibrations, which may differ among horses. Riding some horses may improve the ability of children to respond with an appropriate action depending on the situation (Go reaction) or use self-control appropriately (No-go reaction), possibly through the activation of the sympathetic nervous system.